Teachers' attitudes and perceptions for alternative assessment techniques: a case study of Pakistani universities. (10th April 2011) - Iqbal, Assad; Manarvi, Irfan Anjum
Assessment is one of the crucial components of any education system. Introduction of modern learning theories and advanced researches in education emphasise a shift from traditional to alternative techniques. It helps to effectively assess students' learning outcomes specific with respect to various learning styles. These techniques go beyond traditionally used time-bound paper-pencil tests for assessing students' learning. Stakeholders of this shift are students, teachers and education policy makers. This paper explores current trends of educational assessment in Pakistani universities. It also provides information about attitudes and perceptions of university teachers for using alternative assessment techniques.